A Phenomenological Investigation of Transparency Among Agricultural Influencers on Instagram - Shelby Shank; Jason Headrick; Laura Fischer; David Doerfert (Journal of Applied Communications, 2025)
A phenomenological study explored how agricultural influencers portray transparency on Instagram. Guided by Vroom’s expectancy theory (1964) and opinion leadership, the study used semi-structured interviews with agricultural influencers selected through purposive and snowball sampling. Interview participants shared a common phenomenon of having a background in agriculture as it relates to their presence and transparency on social media. Findings revealed agricultural influencers’ motivations to post about agriculture on Instagram, their definitions of transparency, and how they strive to be transparent in their Instagram posts. Interview responses revealed agricultural influencers are motivated by a desire to authentically share their agricultural experience with followers and bridge the information gap between consumers and producers. Participants defined transparency as being honest, authentic, and relatable, aiming to present an accurate portrayal of agriculture without misinterpretation. This study revealed agricultural influencers foster trust with their followers and strive for open conversations while maintaining personal boundaries of sharing their daily lives on social media. As opinion leaders, results indicated agricultural influencers’ motivations and definitions of transparency align with existing literature. We recommend establishing a definition of agricultural transparency and the development of advocacy resources available to facilitate the communication of agricultural information to consumers. Future research is also recommended in examining agriculture influencers in specific niches or commodities of agriculture, as well as the examination of transparency of agricultural influencers from the consumer perspective.
Keywords: agricultural influencer; phenomenology; social media; Vroom’s Expectancy Theory; opinion leadership; trust; transparency